The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
+2 votes
491 views

asked in Computer Networks by Loyal (7.9k points) | 491 views

2 Answers

+7 votes
Best answer

$A = KP(1-P)^{K-1}$

For the maximum value of $A$, $\frac{dA}{dP}=0$

Solving, we have

$P(K-1)(1-P)^{K-2} = (1-P)^{K-1}$

$P=\frac{1}{K}$


Hence, $A =\lim_{K\rightarrow \infty } (1-\frac{1}{K})^{K-1} = \frac{1}{e}$

answered by Veteran (50k points)
selected by
0 votes
ans is 1/e
answered by (125 points)


Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true

36,194 questions
43,647 answers
124,088 comments
42,928 users